Analysis on the Influence of Cultural Platformization on the Korean Local Screen Industry Empowered by Streaming Media - Yan, Yuting (Transactions on Social Science, Education and Humanities Research, 2026)
Netflix Reorganises the Korean local-content production industry by using a platform model. It is believed that the industrial logic of Korean screen production has been altered by platformisation, and consequently, the arrangement of commissioning, distribution, visibility, etc. has changed. Netflix expands globally and produces original content, but at the same time, it has consolidated data, recommendations and bargaining power. Based on the Korean case, the paper indicates that streaming media has the following dual effects: on the one hand, it helps local screen industries to expand overseas; on the other hand, it increases their dependence on platform infrastructure. Based on verified academic resources and official industry data, this paper analyzes changes in culture production and labour organization due to platformisation.